2013
DOI: 10.1161/atvbaha.112.300287
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antiatherogenic Role of BMP Receptor II in Endothelial Cells

Abstract: Objective Atherosclerosis is an inflammatory disease with multiple underlying metabolic and physical risk factors. Bone morphogenic protein 4 (BMP4) expression is increased in endothelium in atherosclerosis-prone regions and is known to induce endothelial inflammation, endothelial dysfunction and hypertension. BMP actions are mediated by two different types of BMP receptors (BMPRI and II). Here we show a surprising finding that loss of BMPRII expression causes endothelial inflammation and atherosclerosis. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 54 publications
6
81
0
5
Order By: Relevance
“…In contrast to the proinflammatory role of BMPs, a recent study by Kim et al (17) demonstrated that BMPRII plays a constitutively antiinflammatory and antiatherogenic role in ECs. Loss of BMPRII expression causes endothelial inflammation and atherosclerosis (17). In the present study, we did not attempt to define the in vivo role of BMPRII in endothelial and vascular functions.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the proinflammatory role of BMPs, a recent study by Kim et al (17) demonstrated that BMPRII plays a constitutively antiinflammatory and antiatherogenic role in ECs. Loss of BMPRII expression causes endothelial inflammation and atherosclerosis (17). In the present study, we did not attempt to define the in vivo role of BMPRII in endothelial and vascular functions.…”
Section: Discussionmentioning
confidence: 91%
“…For example, differential methylation seems to explain the cell-specific expression of the superoxide dismutase, and the endothelial nitric oxide synthase genes (26,27). Other studies, however, have shown similarities in PAEC and systemic EC dysfunction studied in relation to loss of BMPR2 (19,28), and to PAH in general (29). Here, we provide evidence for the first time that IPAH/HPAH PAEC and iPSC-EC from the same individuals have similar functional impairment related at least in part to reduced BMPR2 and downstream signaling, and gene expression of COL4A2.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance is linked to increased production of IL-6 and IL-8, as the normal growthinhibitory effect of transforming growth factor-b is restored by coincubation with neutralizing antibodies to either IL-6 or IL-8 (35). In addition, siRNA-mediated knockdown of BMPR-II increased monocyte adhesion and induced intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 levels in human umbilical vein endothelial cells (36). Burton and colleagues (37) showed enhanced leukocyte transmigration through BMPR-II-deficient endothelial cells compared with mock-transfected controls.…”
Section: Discussionmentioning
confidence: 99%